HIDROLOGICAL AND HYDRAULIC STUDY OF CITEPUS â CIKAKAK â CIKAPUNDUNG CANAL FLOOD - Anggraeni, Suci
Flood is one of natural phenomena that often bring loss property and life. Mostly, it occurs during a high intensity rainfall event in the catchment area which results in high river flow that cannot be accommodated by river cross sections. Several locations in the area of Bandung City are often flooded such as the Pagarsih, Astana Anyar, and Babakan Irrigation areas. This flood occurred due to the overflow of the Citepus and Cikakak rivers, and the main cause why the flooding is occurred is the cross section river was narrow and the heigh of flood wall at along the rivers was decrease. One of proposed solution to this problem is to construct flood way canal which starting from Citepus river, then crossing Cikakak river and ending at Cikapundung river. This study focused on hydrology and hydraulic analysis of Canal flood. For hydrological analysis is carried out to calculate the planned flood discharge and the hydraulic analysis is carried out modeliing unsteady flow conditions using the SWMM program, and modelling of 3D flow patterns around flow divider using 3D Flow program. The canal flood is design for three alternative location and to accommodate the discharge of flood 50 years periode of Citepus and Cikakak rivers, which is 49.97 m3/s for Citepus and 21.55 m3/s for Cikakak. Base on hydraulic analysis, design of canal flood which pass the road of Jalan Kebon Kawung can reduction flood discharge about 54.2% at Citepus river and 46% at Cikakak river. For design of canal flood which pass the Jalan Paskal-Stasiun also can reduction flood discharge about 66.65% at Citepus river and 52.21% at Cikakak river, also design of canal flood which pass the Jalan Industri-Stasiun can reduction flood discharge about 23.97% at Citepus river and 68.38% at Cikakak river. From three alternative location, Jl. Industri- Stasiun is the best location to applied in Bandung area which focused reduction of flood.